Development and validation of analysis method for sennoside B in Cassia angustifolia using UPLC-MRM/MS - Amrianto; Kurnia Nastira Ningsih; Sumail Sidik Ode Ishak; Ula Aulia Fitrian; Syefira Salsabila; Diah Astari Salam (Institut Teknologi Bandung, 2023)
Cassia angustifolia is a commonly found wild plant from the family Caesalpinaceae that originates from Yemen and Hadramaut province in Southern Arabia, where it is called Arabian senna. The leaves of the plant have been used to treat a variety of ailments such as constipation, malaria, anemia, loss of appetite, and indigestion. Sennosides A and B are the major glycosides found in the leaves and pods of C. angustifolia and are important ingredients in purgative medicines. These compounds are considered as the major active components of Cassia plants and are responsible for their therapeutic activities. To assess the quality and quantity of sennosides A and B, an appropriate analytical method is required, which must be simple, accurate, precise, and widely used. The UPLC-ESI-MRM/MS method was used in this study to validate the analytical method in determining the contents of Sennoside B in senna leaves extract. The validation parameters included specificity, system suitability, linearity, sensitivity (LOD, LOQ), accuracy, and precision. The results indicated that the optimization of MRM using the direct infusion method provided good separation when eluted using liquid chromatography. The validation parameters for system suitability obtained RSD under 2%. The linearity of sennoside B showed excellent results (R2 = 0.999) in the concentration range of 0.98–62.5 µg/ml. The LOD and LOQ values of sennoside B were 0.011 µg/mL and 0.034 µg/ml, respectively. The accuracy values of sennoside B met the predetermined criteria, with RSD < 2% and % recovery of 97-102%. The quantitative analysis revealed that Cassia angustifolia extract contained 0.43 ±0.06 mg/g of sennoside B.